Optimalisasi Pendokumentasian Asuhan Keperawatan - Wahyuni, Tyas; Hariyati, Rr. Tutik Sri; Kuntarti, Kuntarti; Afriani, Tuti; Nasri, Khairul (Journal of Telenursing (JOTING), 2024)
This study aims to identify and analyze problems in the implementation of freezing documentation using the role and function of freezing management approach, as well as problem-solving options. The research method uses case studies through interviews, observations, problem analysis with fishbone diagrams and then compiling innovations. The results of the study showed that documentation of accommodation in the inpatient room of Hospital X before implementation was 45% and after implementation it became 55%, there was an increase especially in the preparation of the closing diagnosis and protection action plan. In conclusion, the documentation process increased by 10% through the Flipbook SAK (Nursing Care Standards) innovation, this shows that the implementation carried out is quite effective in improving the quality of protection documentation. Keywords: Nursing Management, Nursing Care Documentation, Nursing Care Standards